The Calcium-Sensing Receptor and the Reproductive System - Ellinger, Isabella (Frontiers in Physiology, 2016)
Active placental transport of maternal serum calcium (Ca2+) to the offspring is pivotal for proper development of the fetal skeleton as well as various organ systems. Moreover, extracellular Ca2+ levels impact on distinct processes in mammalian reproduction. The calcium-sensing receptor (CaSR) translates changes in extracellular Ca2+-concentrations into cellular reactions. This review summarizes current knowledge on the expression of CaSR and its putative functions in reproductive organs. CaSR was detected in placental cells mediating materno-fetal Ca2+-transport such as the the murine intraplacental yolk sac and the human syncytiotrophoblast. As shown in casr knock-out mice, ablation of CaSR downregulates transplacental Ca2+-transport. Receptor expression was reported in human and rat ovarian surface epithelial cells, where CaSR activation stimulates cell proliferation. In follicles of various species a role of CaSR activation in oocyte maturation was suggested. Based on studies in avian follicles, the activation of CaSR expressed in granulosa cells may support the survival of follicles after their selection. CaSR in rat and equine sperms was functionally linked to sperm motility and sperm capacitation. Implantation involves complex interactions between the blastocyst and the uterine epithelium. During early pregnancy, CaSR expression at the implantation site as well as in decidual cells indicates that CaSR is important for blastocyst implantation and decidualization in the rat uterus. Localization of CaSR in human extravillous cytotrophoblasts suggests a role of CaSR in placentation. Overall, evidence for functional involvement of CaSR in physiologic mammalian reproductive processes exists. Moreover, several studies reported altered expression of CaSR in cells of reproductive tissues under pathologic conditions. However, in many tissues we still lack knowledge on physiological ligands activating CaSR, CaSR-linked G-proteins, activated intracellular signaling pathway and functional relevance of CaSR activation. Clearly, more work is required in the future to decode the complex physiologic and pathophysiologic relationship of CaSR and the mammalian reproductive system.